Analysis Of 12- Level Cycloconverter To Minimize Thd (Total Harmonic Distortion) Level In 3-Phase Induction Motor - et. al., Mallepally Narendar Reddy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
These harmonics are higher than essential frequencies and cause Total Harmonics Distortion (THD) which increases the rms current and generates more warmth in the load. Numerous techniques are used to suppress the harmonics to limit the warmth in the load. Another procedure is utilized in this work to limit THD and the method to beat the low exhibition of a traditional PWM (pulse width tweak) control. In this work, the desired output voltage is accomplished by contrasting the desired sinusoidal waveform (adjusting signal) with a high frequency three-sided waveform (transporter signal). Industrial applications demands high force and long life expectancy motor drives. Three phase motor drives have restricted force density consequently Multiphase motor drives are better solutions for high force density and substantial loads. In this work a 12 level cycloconverter is designed to drive three Phase load. The loads used in the industries almost nonlinear loads like motors. Thusly, because of these nonlinear loads extra harmonics incited at the output of the 12 level cycloconverter drive with major frequency. The harmonics and THD got using our proposed technique is thought about using Mat lab/Simulink